2000
DOI: 10.1002/1097-4652(200101)186:1<116::aid-jcp1005>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide donors regulate nitric oxide synthase in bovine pulmonary artery endothelium

Abstract: This study examined the notion that exogenous generation of nitric oxide (NO) modulates NOS gene expression and activity. Bovine pulmonary artery endothelial cells (BPAEC) were treated with the NO donors, 1 mM SNAP (S-nitroso-N-acetylpenicillamine), 0.5 mM SNP (sodium nitroprusside) or 0.2 microM NONOate (spermine NONOate) in medium 199 containing 2% FBS. Controls included untreated cells and cells exposed to 1 mM NAP (N-acetyl-D-penicillamine). NOS activity was assessed using a fibroblast-reporter cell assay;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 43 publications
3
17
0
Order By: Relevance
“…This is in agreement with previous studies of in vitro injury where some 60% of the response to the endotheliumdependent vasodilator calcimycin remained (Kennedy et al 2003). A recent study demonstrated that incubation of cultured endothelial cells with NO donors for 2 h can upregulate eNOS gene expression by the cells (Chen et al 2001). In the present study, an identical incubation time had no such effect on eNOS expression and caused no change in NF-κB, a transcription factor involved in upregulation of gene expression.…”
Section: Immunocytochemistrysupporting
confidence: 92%
“…This is in agreement with previous studies of in vitro injury where some 60% of the response to the endotheliumdependent vasodilator calcimycin remained (Kennedy et al 2003). A recent study demonstrated that incubation of cultured endothelial cells with NO donors for 2 h can upregulate eNOS gene expression by the cells (Chen et al 2001). In the present study, an identical incubation time had no such effect on eNOS expression and caused no change in NF-κB, a transcription factor involved in upregulation of gene expression.…”
Section: Immunocytochemistrysupporting
confidence: 92%
“…NOS activity was measured as an increase in cGMP using a fibroblast-reporter cell line (RFL-6) as previously described. 29 Briefly, RFL-6 cells in six-well plates (1 Â 10 6 cells/well) were incubated for 20 min at 371C in HEPES. A 500 ml aliquot of cell particulates from each of the samples (see above) was added to the RFL-6 cells and the mixture was incubated for a further 5 min.…”
Section: Measurement Of No Synthase Activitymentioning
confidence: 99%
“…Also, given the evidence indicating that NO may modulate expression of the varied NOS isoform mRNAs, 96,97 including eNOS itself, it remains possible that the varied in vitro and in vivo models may reflect differences in feedback regulatory mechanisms.…”
Section: Hypoxiamentioning
confidence: 99%